Neuropsychological evidence supporting a neurodevelopmental model of schizophrenia: a longitudinal study - Censits, David M. (Schizophr Res, 1997)
The stability of neuropsychological performance in schizophrenia and its relationship to clinical change was contrasted between 60 patients with schizophrenia (30 first-episode, 30 previously treated) and 38 healthy controls using a comprehensive neuropsychological battery and clinical scales administered at intake and at a 19-month follow-up. Consistent with the neurodevelopmental model of schizophrenia, patients demonstrated deficits in cognitive performance at initial testing and did not show decline at follow-up. There were no differences in neuropsychological performance over time between first-episode and previously treated patients, nor between male and female patients or controls. As expected, patients improved clinically with treatment with respect to both positive and negative symptoms. First-episode patients improved more on the positive symptoms of hallucination and delusion; male and female patients showed equivalent clinical improvement. Clinical improvement correlated positively with neuropsychological change, with improved negative symptomatology accounting for most of the significant correlations.